Alive Pathogenic and Saprophytic Leptospires Enter and Exit Human and Mouse Macrophages With No Intracellular Replication - Santecchia, Ignacio; Bonhomme, Delphine; Papadopoulos, Stylianos; Escoll, Pedro; Giraud-Gatineau, Alexandre; Moya-Nilges, Maryse; Vernel-Pauillac, Frédérique; Boneca, Ivo Gomperts; Werts, Catherine (Frontiers in Cellular and Infection Microbiology, 2022)
Leptospira interrogans are pathogenic bacteria responsible for leptospirosis, a zoonosis impacting 1 million people per year worldwide. Leptospires can infect all vertebrates, but not all hosts develop similar symptoms. Human and cattle may suffer from mild to acute illness and are therefore considered as sensitive to leptospirosis. In contrast, mice and rats remain asymptomatic upon infection, although they get chronically colonized in their kidneys. Upon infection, leptospires are stealth pathogen that partially escape the recognition by the host innate immune system. Although leptospires are mainly extracellular bacteria, it was suggested that they could also replicate within macrophages. However, contradictory data in the current literature led us to reevaluate these findings. Using a gentamicin protection assay coupled to high content (HC) microscopy, we observed that leptospires were internalized in vivo upon peritoneal infection of C57BL/6J mice. Additionally, three different serotypes of pathogenic L. interrogans and the saprophytic L. biflexa actively infected both human (PMA differentiated) THP1 and mouse RAW264.7 macrophage cell lines. Next, we assessed the intracellular fate of leptospires using bioluminescent strains, and we observed a drastic reduction in the leptospiral intracellular load between 3h and 6h post-infection, suggesting that leptospires do not replicate within these cells. Surprisingly, the classical macrophage microbicidal mechanisms (phagocytosis, autophagy, TLR mediated ROS and RNS production) were not responsible for the observed decrease. Finally, we demonstrated that the reduction of the intracellular load was associated with an increase of the bacteria in the supernatant, suggesting that leptospires exit both human and murine macrophages. Overall, our study reevaluated the intracellular fate of leptospires and favors an active entrance followed by a rapid exit, suggesting that leptospires do not have an intracellular lifestyle in macrophages.